PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN TEH BOTOL SOSRO (Studi pada Konsumen Teh Botol Sosro di Wilayah Semarang Barat) - Atika Dewi Lestari, 14.05.51.0019 (Students' Journal of Economic and Management, 2018)
The purpose of this study was to analyze the effect of product quality, price, and promotion on purchasing decisions on Teh Botol Sosto consumers in West Semarang region partially. The type of data used in this study is the primary data. While the techniques used for data collection using questionnaires by asking a number of written questions are used to obtain information and respondents. The samples in this study were consumers who had consumed Teh Botol Sosro, aged at least 18 years, and domiciled in West Semarang as many as 100 people. The sampling technique used purposive sampling. The test tool in this study used multiple linear regression. The results of the analysis can be concluded that: Product Quality has positive and significant affects on purchasing decision. The better the quality of the product, the purchase decision will increase. Price has positive and significant affects on purchasing decision. The better the price, then the purchase decision will increase . Promotion has positive and significant affects on purchasing decision. The better the consumer's perception of promotion, the purchasing decision will increase. Keywords: Product quality, Price, Promotion and Purchase Decision